Auxiliary equations are
"\\frac{dx}{x(y^2+z)}=\\frac{dy}{-y(x^2+z)}=\\frac{dz}{z(x^2-y^2)}"
"\\frac{xdx+ydy-dz}{x^2(y^2+z)-y^2(x^2+z)-z(x^2-y^2)}=\\frac{xdx+ydy-dz}{0}" (1)
"\\frac{\\frac{dx}{x}+\\frac{dy}{y}+\\frac{dz}{z}}{y^2+z-(x^2+z)+(x^2-y^2)}= \n\\frac{\\frac{dx}{x}+\\frac{dy}{y}+\\frac{dz}{z}}{0}" (2)
from (1)
"x^2+y^2-2z=C_1" (3)
from (2)
"log(xyz)=C_2,\\ or \\ xyz=C_3" (4)
parametric equation of straight line is
"(x=t,y=-t,z=1)" (5)
On substituting (5) in (3) and (4) we get
"2t^2-2=C_1,\\ -t^2=C_3"
Eliminating t
"-2C_3-2=C_1,\\ or F(C_1,C_3)=C_1+2C_3+2=0"
Therefor
"x^2+y^2-2z+2xyz+2=0" is integral surface, which contains the straight line.
Answer: x^2+y^2-2z+2xyz+2=0
Comments
Leave a comment